Correlation between upper airway ultrasound and Cormack–Lehane grading during laryngoscopy – A prospective study - Sakshi Jain; Arya, Jayendra; Arvind Rathiya; Sudhakar Dwivedi (Asian Journal of Medical Sciences, 2023)
Background: Securing airway and adequate ventilation after induction of anesthesia is the utmost priority of anesthesiologists, failure of that can lead to hypoxic brain injury and death in a few minutes. Aims and Objectives: The aims of this study were to ascertain the role of ultrasonography in predicting difficult intubation by comparing different ultrasonographic parameters. Materials and Methods: One hundred patients posted for elective surgery under general anesthesia were studied. The study was carried out in two phases. The first phase – during the pre-anesthetic checkup, ultrasonographic measurements of Anterior neck soft-tissue thickness at the level of hyoid (ANS-Hyoid), anterior neck soft tissue thickness at the level of vocal cords (ANS-VC), pre-epiglottic space (Pre-E), distance from the epiglottis to the mid-point of the distance between the vocal cords (EVL), and the ratio of both (PES/EVL) was also done. In the second phase, Cormack–Lehane (CL) grade was noted during intubation. A Chi-square test was applied to correlate ultrasonographic parameters and CL grade. Sensitivity, specificity, an area under the receiver operating characteristic (ROC) curve, negative predictive value, and positive predictive value were calculated for various parameters. Results: In this study among the studied parameter, only ANS–VC was statistically significant in predicting difficult intubation (P<0.0001). ANS-VC >0.32 cm was 93.3% sensitive and 84.7% specific and had Area under the ROC curve of 85% in predicting CL grade 3 and 4 (difficult intubation). Conclusion: USG is a useful tool in predicting difficult intubation. ANS-VC >0.32 cm is a highly sensitive and specific predictor of difficult intubation, while other USG parameters are not indicative of difficult intubation.